Hydrogen Sulfide Attenuates β2-Microglobulin-Induced Cognitive Dysfunction: Involving Recovery of Hippocampal Autophagic Flux - Chen, Si-Min; Yi, Yi-Li; Zeng, Dan; Tang, Yi-Yun; Kang, Xuan; Zhang, Ping; Zou, Wei; Tang, Xiao-Qing (Frontiers in Behavioral Neuroscience, 2019)
Background and Aim Accumulation of β2-microglobulin (B2M), a systemic pro-aging factor, regulates negatively cognitive function. Hydrogen sulfide (H2S), a novel gas signaling molecule, exerts protection against cognitive dysfunction. Therefore, the present work was designed to explore whether H2S attenuates cognitive dysfunction induced by B2M and the underlying mechanism. Materials and Methods The cognitive function of rats was assessed by Y-maze, Novel object recognition (NOR), and Morris water maze (MWM) tests. The levels of autophagosome and autolysosome in hippocampus were observed by transmission electron microscopy. The expression of p62 protein in hippocampus was detected by western blot analysis. Results NaHS (a donor of H2S) significantly alleviated cognitive impairments in the B2M-exposed rats tested by Y-maze test, NOR test and MWM test. Furthermore, NaHS recovered autophagic flux in the hippocampus of B2M-exposed rats, as evidenced by decreases in the ratio of autophagosome to autolysosome and the expression of p62 protein in the hippocampus. Conclusion In summary, these data indicated that H2S attenuates B2M-induced cognitive dysfunction, involving in recovery of the blocked autophagic flux in the hippocampus, and suggested that H2S may be a novel approach to prevent B2M-induced cognitive dysfunction.